Genetic Diversity of Local Greek and Bulgarian Grapevine (Vitis Vinifera L.) Varieties - Maria Papapetrou; Dimitrios Loukovitis; Orestis Papadopoulos; Zoi Kazlari; Anastasia Peristeraki; Slavina Arsenova; Desislava Bardarova; Desislava Doncheva; Serafeim Theocharis; Constantinos Karagiannidis; Stefanos Koundouras; Anastasia Giannakoula; et al. (Diversity, 2020)
The aim of this study was to estimate the genetic diversity of Greek and Bulgarian grapevine varieties with the use of microsatellite markers. The studied samples were collected from various productive vineyards, consisting of eight Greek and nine Bulgarian native varieties. In order to create a genetic profile for each sample, a multiplex PCR reaction method was used amplifying simultaneously seven microsatellite loci. Statistical analysis of data showed that there was a high degree of genetic heterogeneity among most of the varieties studied, highlighting the discriminative power of the chosen set of markers. Moreover, the synonymy of (I) Greek Pamid and Bulgarian Pamid and (II) Greek Zoumiatiko and Bulgarian Dimyat was suggested, as each variety pair had identical allele profiles in all loci examined. Regarding the Greek Mavrud and Bulgarian Mavrud varieties, there was a close genetic relationship between them, however, they did not share common alleles in all microsatellite loci and, therefore, should not be characterized as synonyms. On the other hand, Greek and Bulgarian Keratsouda, which were supposed to be common varieties, were found to be genetically different, supporting that these two varieties should be considered as homonyms. Despite the genotypic assay performed herein, we believe that additional molecular work is needed for the efficient management of Greek and Bulgarian grapevine genepools, as well as to safely suggest any synonym or homonym annotation.